Delinquency among majority and minority youths in Cologne, Mannheim and Brussels: the role of religion - Sarah Carol; Freya Peez; Michael Wagner (Journal of Ethnic and Migration Studies, 2020)
The news about sexual assaults and robbery committed by mostly young North African males on New Year's Eve of 2015/2016 in Cologne and elsewhere went around the world. It triggered a revival of the question of the role religion plays in crime, in particular whether Muslims are more criminal. To answer this question, we investigate ethnic minority and majority youths' delinquency in Cologne, Mannheim (Germany) and Brussels (Belgium) using unique large-scale datasets. Our results indicate that youths in Cologne are not exceptionally violent. In line with previous research, we find that religiosity is overall accompanied by lower levels of delinquency (vandalism, property offence, drug abuse, bullying), particularly among Muslims. However, in the case of violence, we reveal the opposite pattern. Yet, we discover that these acts are primarily committed by youths who describe themselves as religious without practising the abstinent lifestyle (i.e. abstaining from binge drinking) prescribed by some religions.
Keywords: 330; delinquency; religion; abstinence; Islam; Germany